Provider Knowledge and Support of Uterus Transplantation: Surveying Multidisciplinary Team Members - Kirsten A. Riggan, MS, MA; Zaraq Khan, MBBS; Carrie L. Langstraat, MD; Megan A. Allyse, PhD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2020)
Objective: To determine relevant provider opinions on uterus transplantation (UTx). Patients and Methods: We invited 1933 providers in obstetrics and gynecology, transplant surgery, transplant medicine, internal medicine, and family medicine at a large, integrated health care system to complete an online survey containing a series of questions on their attitudes about the ethics and clinical utility of UTx. The survey was open from June 4, 2018, through July 2, 2018. We received 449 responses overall (23.2% response rate). Results: Of 433 physicians who responded, 195 (45.0%) believe that UTx is ethically justified, and just over a third (160 of 446 [35.9%]) would introduce the possibility of UTx to a patient with absolute uterine factor infertility (AUFI). Respondents indicated the risks to donor, recipient, and child carried the most weight in their ethical evaluation and were most supportive of UTx in a patient with congenital uterine absence (334 of 743 [45.0%]; participants were allowed to choose more than one answer). A majority stated that a living or cadaveric donor would be an acceptable donor source (238 of 395 [60.3%]). Conclusion: Provider support for UTx is qualified by safety concerns and its expansion to patient populations other than women with AUFI. This survey suggests that most providers limit their support of UTx to patients with the most demonstrated clinical need, childless women with AUFI.